RABAOC Trials - International Center for Tropical Agriculture (2015)
RABAOC (Reseau de Recherche en Alimentation du Bétail en Afrique Occidentale et Centrale) was established as a collaborative research effort between CIRAD-EMVT, ILCA, CIAT and NARS, to conduct adaptative research on forage species suitable for animal feeding in the humid end sub-humid areas 01 West and Central Africa. Through the RABAOC network, 18 trials have been established with forage germplasm received from CIAT, ILCA and IDESSA, in 9 countries.The objectives of RABAOC were:to study adaptability of forage grasses and legumes to soil, climate and biotic factors of the environments in the humid and subhumid regions of West and Central Africe.to provide farmers and institutions interested in forage production and animal husbandry, forage grasses and legumes adapted to local conditions.to advance forage crop improvement by interchange of techniques, of information and by scientific education.For the first 3 years, the common experimental design for RABAOC trials was that of the RIEPT (International Network for Tropical Pastures Evaluation in Tropical America), modified for African conditions.The results presented in this dataset only pertain to the initial evaluation of the forages by the national scientists within the RABAOC network who forwarded their results to CIAT.